Anomalous temperature-dependent strength of copper alloy manufactured by laser-beam powder bed fusion - Dasom Kim; Naoki Takata; Junji Umeda; Toshihiko Shimizu; Makoto Kobashi (Additive Manufacturing Letters)
This study reports an anomalous temperature-dependent tensile behavior of laser-beam powder bed fusion (PBF-LB) processed Cu–Cr–Zr alloy. The yield strength of the alloy initially decreases as the temperature increases to 200±5 MPa and then increases to 350±11 MPa at 500°C before reducing to 234±6 MPa at 600°C. The microstructure consists of elongated Cu grains with a high concentration of Cr solute (∼1 mass%), resulting from rapid solidification during the PBF-LB process. Transmission electron microscopy for the specimens deformed at 500°C revealed the presence of numerous nanoscale Cr-rich particles embedded inside the supersaturated solid solution of the Cu matrix. Nanoscale particles can act as barriers to dislocation motion, leading to an increase in internal stress during plastic deformation at elevated temperatures. This work provides the high potential of post heat treatments for achieving superior mechanical performance using high solute supersaturation formed by the PBF-LB process.